2020
DOI: 10.1037/xhp0000861
|View full text |Cite
|
Sign up to set email alerts
|

Task constraints act at the level of synergies and at the level of end-effector kinematics in manual reaching and manual lateral interception.

Abstract: To coordinate the redundant degrees of freedom (DOF) in the action system, synergies are often proposed. Synergies organi e DOF in temporary task-specific units emerging from interactions amongst task, organism, and environmental constraints. We examined whether task constraints affect synergies, end-effector kinematics, or both. To this end, we compared synergies and end-effector kinematics when participants (N = 15) performed discrete movements of identical amplitude in manual reaching (stationary targets) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
(174 reference statements)
0
3
0
Order By: Relevance
“…First, our earlier studies regarding synergies in rod reaching (Valk et al, 2016;van der Steen and Bongers, 2011) can be taken one step further. A defining characteristic of a synergy is not just co-variation of joint angles, but also the actual location in joint space where the synergy emerges (Tuitert et al, 2020;Wissing et al, 2020). Studying whether, and if so how, the location in joint space where the synergy emerges depends on the tool's properties could further our understanding of the roles of tool constraints in the emergence of synergies.…”
Section: What Psychological Processes Are Involved In Tool Use?mentioning
confidence: 99%
“…First, our earlier studies regarding synergies in rod reaching (Valk et al, 2016;van der Steen and Bongers, 2011) can be taken one step further. A defining characteristic of a synergy is not just co-variation of joint angles, but also the actual location in joint space where the synergy emerges (Tuitert et al, 2020;Wissing et al, 2020). Studying whether, and if so how, the location in joint space where the synergy emerges depends on the tool's properties could further our understanding of the roles of tool constraints in the emergence of synergies.…”
Section: What Psychological Processes Are Involved In Tool Use?mentioning
confidence: 99%
“…First, our earlier studies regarding synergies in rod reaching (Valk et al, 2016;van der Steen and Bongers, 2011) can be taken one step further. A defining characteristic of a synergy is not just co-variation of joint angles, but also the actual location in joint space where the synergy emerges (Tuitert et al, 2020;Wissing et al, 2020). Studying whether, and if so how, the location in joint space where the synergy emerges depends on the tool's properties could further our understanding of the roles of tool constraints in the emergence of synergies.…”
Section: What Psychological Processes Are Involved In Tool Use?mentioning
confidence: 99%
“…Note that task constraints affect the shape of these energy gradients, and thus the location on the UCM at which the task is performed. For instance, reaching to a target or intercepting an object at that same target location implies different task constraints and Tuitert et al [2] showed that the joint angle configuration in the arm at the target was at a different location on the UCM for the two tasks. This indicates that different constraints affect the RCs at different levels and create energy gradients in spaces of elemental variables.…”
mentioning
confidence: 99%